(3CSGdjH GdGSJKeGQ (B-(3GdGSJUfGY (B-(3GdeTGQcI GdeJfGbUI(B((3GdefJgjI HGdJedjc(B)s - (3hGFd(B, (3YQHjGJs ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B,s, 2006)
(3GdeTGQcI GdeJfGbUI (B: (3GdeTGQcI GdeJfGbUI (B"(3GdefJgjI HGdJedjc(B" -(3eMd GdeTGQcI GdeJfGbUI hTQhWgG (B-(3GdGKGQ GdeJQJHI Ydi YbO GdTQcI GdeJfGbUI(B"(3GdGdJReGJ GdeJHGOdI Hjf GdWQajf(B" -(3GdJWHjbGJ GdYedjI GdeYGUQI dYbO GdTQcI GdeJfGbUI (B-(3GdGSJUfGY(B:(3YbO GdGSJUfGY aj Gdabg GdGSdGej (B-(3YbO GdGSJUfGY aj GdfXGe GdeUQaj GdGSdGej (B-(3GdJCUjd GdTQYj dYbO GdGSJUfGY aj GdfXGe GdeUQaj GdGSdGej (B-(3CMcGe YbO GdGSJUfGY aj GdfXGe GdeUQaj GdGSdGej (B-(3GdGKGQ GdeJQJHI Ydi YbO GdGSJUfGY aj GdfXGe GdeUQaj GdGSdGej (B-(3JWHjbGJ YbO GdGSJUfGY aj GdeUGQa hGdeDSSGJs
(3HHdjhZQGajG(B: (3U(B.355s
Keywords: (3GdGSJKeGQ GdeUQajs; (3GdHfhc GdESdGejIs